P76 Skip laminectomy versus cervical laminectomy, an analysis of patient reported outcomes, spinal alignment and re-operation rates: the leeds spinal unit experience (2008–2016). Issue 3 (14th February 2019) - Robins, JMW; Luo, L; Mallallah, F; Timothy, J; Pal, D; Derham, C; Selvanathan, SK
Abstract : Objectives: To compare clinical, radiological and complication results between skip laminectomy and cervical laminectomy for posterior cervical decompression for cervical spondylotic myelopathy. Design: Retrospective single institution cohort study. Subjects: Subjects underwent primary skip or cervical laminectomy between 2008–2016. Methods: Statistical analysis compared pre- and post-operative differences in Visual Analogue Scale, Neck Disability Index and radiological differences in sagittal alignment of the vertebral bodies. Analysis of re-operation rates was performed. Results: A total of 42 and 29 patients had skip and cervical laminectomy respectively. Median follow up was 32±23.1 (Range: 1–325) weeks. Post-operatively there was no difference in patient reported outcomes namely Visual Analogue Scale and Neck Disability Index between skip laminectomy and cervical laminectomy groups compared to pre-operatively (p=0.64, p=0.75). No difference was seen in sagittal alignment between both groups following surgery (p=0.65). Three patients (7.1%) in the skip laminectomy group and two patients (6.9%) in the cervical laminectomy group required revision surgery to the cervical spinal region at a different level to the original surgery. No patients needed further instrumentation. Conclusions: Both skip laminectomy and cervical laminectomy appear to deliver similar outcomes with regards to patient reported outcomes, preserving sagittal alignment and re-operation rates over this short follow-up period.